(untitled) (African Journal of Biomedical Research, 2021)
Cardiovascular function encounter changes on exposure to altitude. High altitude hypoxia (HAH), is the fall in arterial blood oxygen saturation due to low amount of breathable oxygen caused by low atmospheric pressure at high altitude. The human body is capable of adapting to HAH via short and long term mechanisms. HAH affects the vascular tone of pulmonary and systemic vessels thereby increasing ventilation, which is the first notable change at high altitude (HA). Acute exposure to altitude increases cerebral and coronary blood flow and causes pulmonary hypertension. Pulmonary hypertension, is characterized by an increase in pulmonary vascular resistance secondary to hypoxia-induced vasoconstriction and vascular remodeling. Initially exposure to HA decreases systolic blood pressure which increase on activation of sympathetic nervous system. This also is responsible for the increase in heart rate and cardiac output which returns to normal few days after acclimatization but heart rate remains increased while stroke volume remains decreased. The adaptation of the cardiovascular system to chronic exposure to hypoxia involves both structural and functional changes. These include; right ventricle (RV) hypertrophy, persistent pulmonary hypertension, lower CBF and reduced uteroplacental and fetal volumetric blood flows. This review focuses on cardiovascular adaptation to high altitude exposure.